Differentiation of the body build in judo competitors of the men`s Polish national team - Jagiello, W. (Archives of Budo, 2013)
Background and Study Aim: Anthropologists' research repeated for over half a century now prove that the body build constitutes one of the elements differentiating sportsmen from persons not carrying out a systematic physical training. However, in the population of sportsmen one deals with the accumulation two factors - features of persons selected to practise a particular sport (thus with the greatest predispositions) and the results of training. The aim of the study was to properties of the body build among judo competitors of the national team compared to persons of the same population not practising professional sport. Material and Methods: The study involved competitors from the Polish national team in men`s judo (n = 14). Competitors` age 20-30 (x = 23 years), body mass 63 kg to 160 kg (x = 93.8 kg), body height 166-197 cm (x = 179.3 cm), training experience 13±4.2 years. The reference group was made up of students of Warsaw Technical University (Poland). Eighteen basic somatic features were measured. Slenderness, Rohrer`s, BMI, and Manouvrier`s indices were calculated. Body density, complete body fat, active tissue, overall profile of the body build and internal proportions of the body build were determined. Results: Weight categories (with the increase in body mass, a distinct decrease in slenderness features takes place) are an important factor determining morphological differentiation of judo competitors. Proportions of features of factors analysed internally show that competitors of all weight categories are characterised by particularly strong muscles of the forearm and weak ones of the shank. Conclusions: A selection of an appropriate technique of fight (throws, grips, feints and their combinations) to the body build and other components of the judo competitor`s personality still remains an open issue. These problems must be tackled by coaches in reference to particular competitors individually.